Pengaruh Proporsi Kacang Merah Dan Suhu Pengovenan Terhadap Karakter Brownies Kacang Merah (Phaseolus Vulgaris L.) - Yosua Fernando H (BiSTeK Pertanian, 2025)
Red beans (Phaseolus vulgaris L) belong to the group of peas (legume). The technology of shading is one of the alternative processes of semi-finished products that are recommended because they are more durable to be stored. There are two types of brownies, steamed brownies and oven brownies. Red bean flour can replace 10% wheat flour in making brownies and can replace 20% flour in the manufacture of sponge cake products. Increased oven temperature will increase development volume and texture. The purpose of this study was to determine the proportion of red bean flour and oven temperature to the character of red bean brownies. The factorial 2-factor study design was arranged in a Randomized Block Design (RBD). The observation variable consisted of antioxidant activity, hardness, protein, crude fiber, organoleptic test (flavor, aroma, texture. Proportion 1 factor T0 (0 gr red bean flour + 100 gr flour), T1 (50 gr red bean flour + 50 gr wheat flour), T2 (70 grams of red bean flour + 30 grams of flour) 2. Factor 2 oven temperature (160, 180, 220 ˚ C) The chosen treatment is the proportion of red bean flour 70 gr + wheat flour 30 grams and oven temperature 160 ˚C with antioxidant activity (42.8%), Hardness (0.96 N), Protein (9.7%), Crude fiber (3.6%), and panelist preference for Aroma value (4,33) , Taste (4.43), and Texture (4.33).